A plant’s perception of growth-promoting bacteria and their metabolites - Abou Jaoudé, Renée; Luziatelli, Francesca; Ficca, Anna Grazia; Ruzzi, Maurizio (Frontiers in Plant Science, 2024)
Many recent studies have highlighted the importance of plant growth-promoting (rhizo)bacteria (PGPR) in supporting plant's development, particularly under biotic and abiotic stress. Most focus on the plant growth-promoting traits of selected strains and the latter's effect on plant biomass, root architecture, leaf area, and specific metabolite accumulation. Regarding energy balance, plant growth is the outcome of an input (photosynthesis) and several outputs (i.e., respiration, exudation, shedding, and herbivory), frequently neglected in classical studies on PGPR-plant interaction. Here, we discuss the primary evidence underlying the modifications triggered by PGPR and their metabolites on the plant ecophysiology. We propose to detect PGPR-induced variations in the photosynthetic activity using leaf gas exchange and recommend setting up the correct timing for monitoring plant responses according to the specific objectives of the experiment. This research identifies the challenges and tries to provide future directions to scientists working on PGPR-plant interactions to exploit the potential of microorganisms' application in improving plant value.